A new cryptic species of Ameerega (Anura: Dendrobatidae) from Brazilian Cerrado - Vaz-Silva, Wilian; Maciel, Natan Medeiros (Zootaxa, 2011)
A new cryptic species of poison frog is described from Central Brazil and included in the Ameerega picta group. Ameerega berohoka sp. nov. occurs in cerrado sensu stricto and gallery forest phytophysiognomies in the Cerrado biome in areas drained by the Araguaia River basin, State of Goiás, Brazil. The new species differs from the other species in the A. picta group by adult morphology, such as dorsal coloration, hand length, nostril shape, and features of advertisement call. Uncorrected p-distances of a fragment of the 16S mitochondrial rRNA gene revealed high divergence among other Ameerega species. The new species seems to be genetically most similar to Ameerega flavopicta (ca. 5.3%).